Paper Communicating Without Words: Focus on Malaysians - Wong, Ngan Ling; Kuang, Ching Hei; David, Maya Khemlani (2010)
Japan is a socially constructed society with group-orientation and social interdependence play an important role in Japan. Communication without words (silence) is possible and preferable (Wong, 2005). For instance keeping quiet to show deference or respect to others or, to maintain harmony in certain situation; are highly valued in Japanese society. Is silence a salient feature in discourse among the various ethnic groups in multiracial Malaysia? This is the focus of this study. This study looks at how the three dominant ethnic groups of Malaysia view ‘silence’ as a tool in communication. Data is analyzed using SPSS and findings are presented in two sections.